Dexamethasone induces the expression of LRRK2 and α-synuclein, two genes that when mutated cause Parkinson’s disease in an autosomal dominant manner - Park, Ji-Min (Korean Society for Biochemistry and Molecular Biology, 2013)
LRRK2 (leucine-rich repeat kinase 2) has been identified as a gene corresponding to PARK8, an autosomal-dominant gene for familial Parkinson’s disease (PD). LRRK2 pathogenicspecific mutants induce neurotoxicity and shorten neurites. To elucidate the mechanism underlying LRRK2 expression, we constructed the LRRK2-promoter-luciferase reporter and used it for promoter analysis. We found that the glucocorticoid receptor (GR) transactivated LRRK2 in a ligand-dependent manner. Using quantitative RT-PCR and Western analysis, we further showed that treatment with dexamethasone, a synthetic GR ligand, induced LRRK2 expression at both the transcriptional and translational levels, in dopaminergic MN9D cells. Dexamethasone treatment also increased expression of α-synuclein, another PD causative gene, and enhanced transactivation of the α-synuclein promoter-luciferase reporter. In addition, dexamethasone treatment to MN9D cells weakly induced cytotoxicity based on an LDH assay. Because glucocorticoid hormones are secreted in response to stress, our data suggest that stress might be a related factor in the pathogenesis of PD. [BMB Reports 2013; 46(9): 454-459]